2022
DOI: 10.48550/arxiv.2202.09608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radial velocity variability and evolution of hot subdwarf stars

S. Geier,
M. Dorsch,
I. Pelisoli
et al.

Abstract: Hot subdwarf stars represent a late and peculiar stage in the evolution of low-mass stars, because they are likely formed by close binary interactions. Here we performed a radial velocity (RV) variability study of a sample of 646 hot subdwarfs with multi-epoch radial velocities from Sloan Digital Sky Survey (SDSS) and Large Sky Area Multi-Object Fibre Spectroscopic Telescope (LAMOST) spectra. Atmospheric parameters and RVs were taken from the literature. For stars with archival spectra but without literature v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Hence, we could not obtain a deeper conclusion on this field before the binary nature of the sample are confirmed. Geier et al (2022) studied radial velocity (RV) variability for a sample of 646 hot subdwarfs with multi-epoch radial velocities from SDSS and LAMOST. They found that only a small fraction (e.g., ≈ 3%, see Section 3 and Fig 2 in their study) of He-rich hot subdwarf stars (i.e., log(nHe/nH) -1) show RV variability, while a much higher fraction of He-poor hot subdwarf stars (i.e., log(nHe/nH) <-1) presents RV variability (e.g., ≈ 30%).…”
Section: Hints For Binarity In Composite Spectrum Hot Subdwarf Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we could not obtain a deeper conclusion on this field before the binary nature of the sample are confirmed. Geier et al (2022) studied radial velocity (RV) variability for a sample of 646 hot subdwarfs with multi-epoch radial velocities from SDSS and LAMOST. They found that only a small fraction (e.g., ≈ 3%, see Section 3 and Fig 2 in their study) of He-rich hot subdwarf stars (i.e., log(nHe/nH) -1) show RV variability, while a much higher fraction of He-poor hot subdwarf stars (i.e., log(nHe/nH) <-1) presents RV variability (e.g., ≈ 30%).…”
Section: Hints For Binarity In Composite Spectrum Hot Subdwarf Starsmentioning
confidence: 99%
“…Note that, all the stars analyzed by Geier et al (2022) were single-lined hot subdwarf stars, while composite hot subdwarfs were not included. We cross-matched our 131 composite hot subdwarfs identified with LAMOST DR8 LRS Multiple Epoch Catalog, in which 7,912,959 sources with 2 times or more multiple observations were collected, and found 61 common records.…”
Section: Hints For Binarity In Composite Spectrum Hot Subdwarf Starsmentioning
confidence: 99%